Analisis Yuridis terhadap Penerapan Hak Cipta sebagai Objek Jaminan Fidusia dalam Pemberian Fasilitas Kredit pada Perbankan di Kota Batam - Agustianto Agustianto; Yeny Sartika (Journal of Judicial Review, 2019)
The application of copyright as an object of fiduciary collateral in the world is still constrained by several obstacles. So that until now there are still no financial institutions that carry out these provisions. Because the financing institution has only received movable and tangible material objects that can be seen directly and have high economic value. This can guarantee the credit taker / debtor fulfills the performance in accordance with the credit agreement agreed upon by the parties. However, copyright regulations have allowed copyrights to be tied to fiduciaries. Because copyright contains elements of economic rights. The research method used in the study is empirical, supported by the results of interviews with several speakers among notaries, lawyers and legal consultants, financial institutions (commercial banks and BPR), and the Regional Office of Menkumham, the primary data from this study. As well as to strengthen the opinions of the resource persons to disburse supporting data through library studies as secondary data. After collecting all the managed data and analyzing using a qualitative method that is classifying each data obtained in accordance with the research aspects. Finally draw conclusions by describing them descriptively. Guided from this research the results obtained are copyright as objects of fiduciary security constrained by the absence of copyright as one of the collateral for loans in Bank Indonesia Regulations, and the Fiduciary Guarantee Act regarding the regulation of intangible moving objects is less significant. In addition, there is no valuation institution that serves to assess the economy owned by a copyright.